Carvacrol and human health: A comprehensive review. (9th May 2018) - Sharifi‐Rad, Mehdi; Varoni, Elena Maria; Iriti, Marcello; Martorell, Miquel; Setzer, William N.; del Mar Contreras, María; Salehi, Bahare; Soltani‐Nejad, Azam; Rajabi, Sadegh; Tajbakhsh, Mercedeh; Sharifi‐Rad, Javad
Abstract : Carvacrol (CV) is a phenolic monoterpenoid found in essential oils of oregano ( Origanum vulgare ), thyme ( Thymus vulgaris ), pepperwort ( Lepidium flavum ), wild bergamot ( Citrus aurantium bergamia ), and other plants. Carvacrol possesses a wide range of bioactivities putatively useful for clinical applications such antimicrobial, antioxidant, and anticancer activities. Carvacrol antimicrobial activity is higher than that of other volatile compounds present in essential oils due to the presence of the free hydroxyl group, hydrophobicity, and the phenol moiety. The present review illustrates the state‐of‐the‐art studies on the antimicrobial, antioxidant, and anticancer properties of CV. It is particularly effective against food‐borne pathogens, including Escherichia coli, Salmonella, and Bacillus cereus . Carvacrol has high antioxidant activity and has been successfully used, mainly associated with thymol, as dietary phytoadditive to improve animal antioxidant status. The anticancer properties of CV have been reported in preclinical models of breast, liver, and lung carcinomas, acting on proapoptotic processes. Besides the interesting properties of CV and the toxicological profile becoming definite, to date, human trials on CV are still lacking, and this largely impedes any conclusions of clinical relevance.